Changing the development paradigm in African agricultural water management to resolve water and food challenges. Issue 7 (17th November 2021) - Bjornlund, Henning; van Rooyen, Andre; Pittock, Jamie; Bjornlund, Vibeke
ABSTRACT: Meeting growing demand for water and food in Africa, and other parts of the Global South, presents a significant and critical challenge over the next 50 years. This paper draws on an ongoing project in Africa to outline the research-for-development work that is urgently required to facilitate a paradigm shift in agricultural water management. Such work should lead to increased productivity and profitability of agricultural water use to allow agriculture to release some water to meet the growing needs of other sectors, while still meeting food security needs and contributing to a prosperous rural population.